THE RELATIONSHIP BETWEEN THE GENERAL AND FINANCIAL STRATEGY OF THE ENTERPRISE - Rakhmatjanov Lazizkhan Turabayevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: The article shows the relationship between general and financial strategic planning. The main aspects of the mutual influence of strategies are revealed. The necessity to consider the financial strategy as a tool for achieving the goals of general planning is formulated. The problems of achieving the planned financial result of innovative development within the framework of the implementation of the general strategy of the enterprise are outlined